Operational Management Analysis in Increasing Company Turnover - Labibah, Hanifah; Sukamto, Dessy; Hadi Prayitno, S.; Salim, Agus; Dwiningwarni, Sayekti (Jurnal Ilmiah Manajemen Kesatuan, 2024)
MSMEs are one effort to reduce unemployment in Indonesia. The development of MSMEs in Indonesia cannot be separated from the following factors, including the use of technological facilities; information and communication; ease of borrowing business capital; reduction in final Income Tax (Pajak Penghasilan/PPh) rates. One of the MSMEs in Mojokerto Regency is Haniprint, a business in the printing and gift sector. This business is a new business, which started in 2020. The aim of this research is to explain the operational management implemented at Haniprint; starting from the customer service process to the order finishing process. This research also explains the influence of implementing operational management on increasing Haniprint's turnover. This study uses a qualitative method. This research method aims to explain the situation of a business in the printing and gift sector in depth and is carried out by collecting as much data as possible. The data collection process was carried out by means of interviews and experiencing processes in the printing and gift sector. The results of the research show that good operational management greatly influences the increase in turnover, but this is not the only factor that influences the increase in turnover. Customer needs in certain months of each year also influence the increase in turnover.